С-Met receptor can be activated by extracellular alkaline medium. (2nd January 2019) - Serova, Oxana V.; Orsa, Alexander N.; Chachina, Natalia A.; Petrenko, Alexander G.; Deyev, Igor E.
Abstract: Receptor tyrosine kinase (RTK) Met or c-Met is a target of hepatocyte growth factor (HGF) and it plays an important role under normal and pathological conditions. Activation of Met signaling pathway is associated with several cellular processes, such as proliferation, survival, motility, angiogenesis, invasion, and metastasis. In this article, we describe the ability of Met to activate upon a mild alkali treatment. To identify potential alkali-regulated proteins, CAKI-1 cells were treated with alkaline media and further tested for protein phosphorylation changes. By anti-phosphotyrosine antibody precipitation and lectin chromatography, we identified Met as a major cytoplasmic membrane protein that responded to pH changes by its phosphorylation. The activation of Met by alkali occurred at pH >8.0 and was dose-dependent. Specificity of the Met response to alkali was confirmed by the treatment with Met kinase inhibitor SU11274 and also by Met receptor knockout using CRISPR/CAS9 genome editing system. Both approaches completely blocked the Met phosphorylation response in CAKI-1 cells. Similar pH-dependent Met activation was observed in the HeLa cell line. Our data suggest existence of ligand-independent mechanism of Met receptor activation.